The Leadership Vision of Charismatic Kyai in the Implementation of Religious Moderation Values in Al-Baqiyatush Shalihat Islamic Boarding School, Jambi Province - Badarussyamsi; Abdul Wahab, Wahyudi; Umar, M. Hasbi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The main focus of this research is to examine the role of charismatic kyai leadership in integrating the values of religious moderation in Islamic boarding schools. This research was conducted using qualitative methods. Data collection was obtained through observation and in-depth interviews. Meanwhile, data analysis is carried out in stages: data reduction, data presentation, and verification and drawing conclusions. The research results show that charismatic kyai use a local cultural approach to convey messages of religious moderation, so that these values are more easily accepted and internalized by the students. Through preserving cultural heritage, kyai utilize local traditions and wisdom as a means of instilling the values of religious moderation, which not only preserves cultural identity but also enriches the spirituality of students with values of tolerance and togetherness. Apart from that, the legitimacy of religious moderation is strengthened through the use of classical Islamic intellectual treasures, where the teachings of previous ulama are used as a basis for developing moderate religious understanding. By referring to the teachings of classical ulama, the kyai succeeded in providing a strong intellectual basis for the implementation of religious moderation, which is in harmony with the rich Islamic tradition. In conclusion, the leadership of the charismatic kyai at the Al-Baqiyatush Shabayar Islamic Boarding School is effective in promoting religious moderation through synergy between cultural preservation and Islamic intellectual treasures.